2016
DOI: 10.1155/2016/9689760
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency in Elderly Patients Admitted to an Inpatient Rehabilitation Unit in Tropical Singapore

Abstract: Background. Data on hypovitaminosis D in elderly patients admitted to rehabilitation units in tropical countries are scarce. Objective. To assess the prevalence of vitamin D deficiency and its associated risk factors in elderly patients admitted to a rehabilitation unit in tropical Singapore. Methods. Prospective, cohort study of 134 subjects ≥ 65 years old admitted to a tertiary rehabilitation centre. Serum 25-hydroxyvitamin D3 (25OHD3) was measured on rehabilitation admission. Results. Mean age was 72.0 ± 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
2
14
0
2
Order By: Relevance
“…Malays, Indians and patients with recurrent falls were at higher risks for vitamin D deficiency [9]. The findings were largely in congruent with the our pilot study, apart from the racial difference.…”
Section: Discussionsupporting
confidence: 89%
“…Malays, Indians and patients with recurrent falls were at higher risks for vitamin D deficiency [9]. The findings were largely in congruent with the our pilot study, apart from the racial difference.…”
Section: Discussionsupporting
confidence: 89%
“…However, almost twice as many women as men were vitamin D deficient, although this difference was not statistically significant. In a study of 134 inpatients ≥65 years old in a rehabilitation centre in Singapore, although 26.9 % reported taking calcium and/or vitamin D supplementation, 44 % were vitamin D deficient, and a further 41.8 % were vitamin D insufficient, with no significant difference in vitamin D levels between those who were taking vitamin D supplementation and those who were not [ 6 ]. These results demonstrate the need for future studies of the effects of age and diabetes mellitus on the bioavailability of vitamin D supplements.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of vitamin D deficiency in Singapore has been reported to be 44 % in an inpatient rehabilitation unit [ 6 ], 34.5 % among patients admitted to a local hospital with hip fractures [ 7 ] and 14.3 % in an ethnic Chinese cohort 45–74 years old [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Before enrollment, patients who met the eligibility criteria on admission were required to provide written informed consent after being provided with an explanation of the study’s aims and procedures by the attending physiatrist. In view of previous findings indicating that almost all elderly patients undergoing rehabilitation have vitamin D deficiency [4,5], we did not include the serum 25-hydroxyvitamin D level as an inclusion criterion. We did not specifically include controls for sun exposure.…”
Section: Methodsmentioning
confidence: 99%
“…In previous research, 86%–89% of elderly patients in a rehabilitation facility were found to have vitamin D deficiency [4,5], and several further studies have reported an association between serum vitamin D levels and functional recovery after stroke [6,7,8,9,10,11,12,13]. Vitamin D is a neurosteroid that is thought to play a neuroprotective role because of the widespread distribution of vitamin D receptors on neuronal and glial cells [14,15].…”
Section: Introductionmentioning
confidence: 99%